How Does Task Presentation Impact Motor Inhibition Performance in Young Children? - Mason, Kathryn; Bowmer, Alice; Welch, Graham F. (Frontiers in Psychology, 2021)
Peg tapping tasks are commonly used as a measure of inhibitory skill in young children. However, differences in the way the task is presented may influence children's performance. For example, if a peg tapping task is presented at regular intervals, children can entrain to the presentation pulse, which may in turn support their performance. This study assessed how different aspects of presentation may support or impair children's results. An experimenter was filmed delivering the tapping task at two different speeds (120bpm and 150bpm). Additionally, they were filmed delivering the task at regular intervals (i.e., the onset of each trial was predictable), or at irregular intervals (the onset of each trial was unpredictable). N=103 children aged between five and six years old were tested on the task. They completed one block with 20 regular interval trials and another block with 20 irregular interval trials. Block presentation order was randomized. Children who achieved over 90% accuracy on the task were then presented with two more blocks at 150bpm. Children’s response accuracy and reaction times were measured. Our results show a difference in children's accuracy across all conditions. The study demonstrates how speed and regularity of presentation can affect children's scores on a tapping task used to measure inhibition. Demands on working memory, motor ability and speed of processing are all affected by adjustments in presentation. Entrainment to a pulse is also an important factor to consider in this context.